Brian Selznick’s The invention of Hugo Cabret, Martin Scorsese’s Hugo, and the theft of subjectivity - Macleod, Mark (SOLETRAS, 2012)
Sanders (2006) and Hutcheon (2006) are among the many adaptation theorists whochallenge the criterion of ‘fidelity’, and yet a frequent response to Martin Scorsese’sAcademy Award-winning film Hugo is that it is faithful to Brian Selznick’s Caldecott Medalwinningbook The invention of Hugo Cabret. This paper argues that in each case the mediumdetermines a significant difference in the construction of subjectivity. The book’spreoccupation with theft indicates a Lacanian concern with the origin of subjectivity and theimplied author’s subtextual guilt about his dependence on the work of another artist. Thefilm’s shift in emphasis to the necessity of relationships and family, however, parallelsKristeva’s assumption that intertextuality is inevitable. As Geraghty (2009) points out,adaptation is by definition dependent on another text. Consequently, Scorsese’s Hugo ignoresthe book’s concern with originality and, at a time when cinema is again being repositioned bytechnological change, celebrates the continuity and heritage of the medium.